Determinants of Contemporary Processes of Economic and Information Globalization of Financial Markets - Dariusz Prokopowicz; Sylwia Gwoździewicz (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
The globalization processes took place many times in the socio-economic and cultural development of transnational communities. One of the last such processes has been occurredsince the middle of the last century. The current globalization process is mainly related with the successively progressing integration of financial markets and with the development of information and communication technologies (ICT) and Internet technologies. The socioeconomic, political and business changes, which have been taken place in the global dimension since the middle of the last century, are a source of modification of the currently functioning market structures and global models of financial systems. The liberalization of capital flows, progressing since the 1970s, has been determined by many economic and political factors, including the modification of the international monetary system. The main determinants of economic and information globalization include such processes as liberalization of capital flows, deregulation of international financial markets and progress in the field of ICT. These processes constituted favorable conditions for the increase in the tendency to globalization of the world economy as well as for the internationalization of financial markets. The processes of globalization in the ancient history were of a slightly different nature. In those days the production of goods was dominated by other factors than it is today and economics has not been yet a separate science.